Evaluating the effectiveness of Work Integrated Learning (WIL) from the perspective of its key stakeholders: a case study of a TVET college - Madabane, Sandisiwe (Rhodes University, Faculty of Commerce, Rhodes Business School)
This research aims to evaluate the effectiveness of a Work Integrated Learning (WIL) programme from the perspective of its key stakeholders, using stakeholder theory as the framework. Stakeholder theory suggests that organisations should consider the interests and needs of various stakeholders who have a vested interest in or are affected by the organisation's activities (Freeman 1963;1984). In the context of WIL, stakeholders include students, the Technical and Vocational Education and Training College, and host employers. The study uncovers the experiences, perceptions, and recommendations of students, educators, employers, and institutions involved in the WIL programme by collecting data through interviews, focus groups, and documents. Through evaluation research, valuable insights emerge regarding the success and potential areas for improvement of WIL within TVET Colleges. The findings indicate issues like inadequate resources and uneven student readiness, and they offer helpful suggestions for better communication, resource distribution, and support systems. Additionally, this calls for more research on curriculum integration, industry collaborations, and long-term career outcomes evaluation.
Keywords: Technical institutes -- South Africa; Vocational education -- South Africa; Work-integrated learning; Stakeholder management; Stakeholder theory